O discurso do corpo na comunicação das marcas - Cortesão, Maria João (2015)
The brands speech  is often based on a metaphorical approach. In this article, we will focus our analysis on the body as a communication vehicle of the Optimus brand, in 2003 and 2008. Our rebrandings lies in four TV commercials , follow what you feel and 3G-Romeo and Juliet (2003) and Optimus-Magma and LifeShare (2008). We are interested in understanding how the body is covered in two moments of turning the brand , and the ‘ creator’ dialogue between the filmic and advertising techniques . It is at this interception codes, we understand that there is a real possibility of brands communicate with their target audience .